COMMUNITY BASED CORRECTION: METODE ALTERNATIF MENGATASI OVERCROWDED - Tobing, Noel Tua Lumban (Fasanesia Library, 2019)
The emergence of the community based correction method begins with the practice of imprisonment which by many countries tends to be seen as the only type of punishment until the longer the prison conditions become overcrowded and actually have a worse impact on the perpetrators. The need for other alternative crimes to avoid more prison construction eventually gave birth to the CBC concept. In review from the SMS data of the director general of PAS laps in march 2020 the number of prison and remand center residents in indonesia was oververcrowded, with a total of 270,415 while its capacity was only 132,531. this proves that alternative crimes are necessary to reduce the number of prison and remand center residents. Community based correction is an alternative method of non-imprisonment which aims to re-assault the perpetrators into the community, in other words the perpetrators are not jailed but serve their sentences in the community so that the community can participate in the guiding process of convicted persons. The study aims to analyze alternative methods of coping with overcrowded. The method used in this study is descriptive with qualitative method as the primary data for researching. And for secondary data conducted a review of libraries and law no. 12 of 1995 on correctional as additional data. The results and conclusions obtained from this study that several basic principles are needed to implement the open prison operational program.